Czy w Polsce rośnie akceptacja społeczna dla nierówności płac? - Kumor, Paweł (Annales. Etyka w Życiu Gospodarczym, 2011)
In our studies we deal with estimating of the optimal ranges of earnings – the optimal of Gini indexes which are favourable tomaximization of the GDP growth in Poland. We suspect that the optimal Gini coefficients expressing the acceptance of the whole of societyfor earnings inequalities can increase.In the article we formulated a hypothesis on the social habit to increasing disproportions of earnings. We verified the hypothesis on thebasis of the model of the economic growth using data from 1970 to 2007. We carried out econometric studies in two stages. In the first stagewe estimated the optimal Gini coefficients for short sub-periods being moved increasingly in time. In the second stage, we studied thecharacter of changes of the optimal Gini coefficients.In the studies we proved the hypothesis on the habit of society to increasing disproportions of earnings. The optimal Gini coefficientsincrease along with the increase of differences in earnings and the increase of the economic level per capita. The growth of the optimal Ginicoefficient may be slowed down.